2004
DOI: 10.1242/jeb.00813
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen metabolism in the African lungfish (Protopterus dolloi)aestivating in a mucus cocoon on land

Abstract: SUMMARY This study aimed to elucidate the strategies adopted by the African slender lungfish, Protopterus dolloi, to ameliorate the toxicity of ammonia during short (6 days) or long (40 days) periods of aestivation in a layer of dried mucus in open air in the laboratory. Despite decreases in rates of ammonia and urea excretion, the ammonia content in the muscle, liver, brain and gut of P. dolloi remained unchanged after 6 days of aestivation compared with the control fasted for 6 days. For speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 27 publications
3
101
0
Order By: Relevance
“…The liver was quickly excised, freeze-clamped with aluminium tongs pre-cooled in liquid nitrogen and kept at −80°C. A group of fish (N=35) was induced to aestivate individually at 27-29°C and 85-90% humidity in plastic tanks (L×W×H, 29×19×17.5 cm) containing 15 ml dechlorinated tapwater (made 0.3‰ with seawater) initially, following the procedure of Chew et al (2004). It took approximately 6-8 days for the fish to be encased in a brown dried-mucus cocoon.…”
Section: Experimental Conditions and Collection Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver was quickly excised, freeze-clamped with aluminium tongs pre-cooled in liquid nitrogen and kept at −80°C. A group of fish (N=35) was induced to aestivate individually at 27-29°C and 85-90% humidity in plastic tanks (L×W×H, 29×19×17.5 cm) containing 15 ml dechlorinated tapwater (made 0.3‰ with seawater) initially, following the procedure of Chew et al (2004). It took approximately 6-8 days for the fish to be encased in a brown dried-mucus cocoon.…”
Section: Experimental Conditions and Collection Of Samplesmentioning
confidence: 99%
“…In nature, aestivation can occur inside a subterranean mud cocoon. In the laboratory, African lungfishes can be induced to aestivate in driedmucus cocoons in air (Chew et al, 2004;Ip et al, 2005;Loong et al, 2005Loong et al, , 2007Loong et al, , 2008aLoong et al, ,b, 2012a. There are three phases of aestivation: induction, maintenance and arousal.…”
Section: Introductionmentioning
confidence: 99%
“…With the onset of the dry season, some lungfish burrow into the mud and secrete a mucus cocoon that surrounds the body to reduce desiccation (see Fishman et al 1986 for review). During both estivation and air exposure, nitrogenous wastes are also converted to and stored in the body as urea, rather than as the more toxic ammonia (Smith 1930(Smith , 1931Janssens 1964;Jans-sens and Cohen 1968;DeLaney et al 1974DeLaney et al , 1977Chew et al 2003Chew et al , 2004Loong et al 2005;Wood et al 2005). Only P. annectens is reported to estivate in nature on a regular basis (Greenwood 1986), but all African lungfish have the ability to secrete a cocoon and to enter an estivation-like state when denied access to water in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike their South American and Australian counterparts, African lungWshes undergo aestivation in the absence of water during drought, and remain incarcerated in this state of inactivity until the return of water to the habitat (Fishman et al 1987;Ip et al 2005a). They can aestivate inside a cocoon made of dried mucus in air (Protopterus dolloi, Chew et al 2004; Protopterus aethiopicus, Ip et al 2005b; Protopterus annectens, Loong et al 2008) or burrow into the mud and aestivate in a subterranean cocoon (Protopterus annectens and P. aethiopicus;Janssens 1964;Janssens and Cohen 1968a, b;Loong et al 2008). African lungWshes are ureogenic; they possess a full complement of ornithine-urea cycle (OUC) enzymes (Janssens andCohen 1966, 1968a;Mommsen and Walsh 1989), including carbamoyl phosphate synthetase III (CPS III), in their livers (Chew et al 2003;Loong et al 2005).…”
mentioning
confidence: 99%
“…Since ammonia is toxic (Cooper and Plum 1987;Hermenegildo et al 1996;Ip et al 2001;Brusilow 2002;Felipo and Butterworth 2002;Rose 2002), African lungWshes have to avoid ammonia toxicity during aestivation, and they achieve this through an increase in urea synthesis (Smith 1930(Smith , 1935Janssens 1964;Janssens and Cohen 1968a, b) and a suppression of N production as ammonia (see Ip et al 2004;Chew et al 2006 for reviews). Recently, Chew et al (2004) demonstrated that the rate of urea synthesis increased 2.4-to 3.8-fold and the rate of N production decreased by 72% in P. dolloi during 40 days of aestivation in air (normoxia) when compared with the immersed control.…”
mentioning
confidence: 99%